Teresa Margolles, Laura Valencia and Fabiola Rayas: a work that confronts violence head-on (REVISTA NODO, 2026)
For more than twenty years, artistic practices have been developing in the public space, in order to make visible the forms of violence that impact Mexican civil society. Initiated by collectives working or not with artists, the use of artistic forms invites us to question what potentialities creation contains, what aesthetics are implemented in the face of violence and with what impacts. The analysis focuses on two generations of women artists who have placed social and political violence at the heart of their practice: Teresa Margolles (1965), Laura Valencia (1979) and Fabiola Rayas (1985). Each portrait aims to understand how art moves from the museum to the street and the changes induced by this movement in terms of elaboration, reception and exhibition. The analysis allows us to question the links between art and artivism, the role played by the body and the originality of the resulting work.
Keywords: Mexico; Teresa Margolles; Laura Valencia; Fabiola Rayas; activism